Zarządzanie procesami logistycznymi w zintegrowanych sieciach logistycznych Kuźni Jawor SA - Skowrońska, Agnieszka (Management of Logistic Processes in Integrated Logistic Networks of Kuźnia Jawor SA, 2005)
This analysis is aimed at presenting the results of a survey concerning methods of management of logistic processes in the network of companies involving Kuźnia Jawor SA. The report contains answers to questions pertaining to the place of the company within the integrated logistic networks, the degree and extent of integration among particular companies, types of logistic processes and the manner in which the set of such processes depends on the concept of competiveness. that is objectives (requirements) which the network as a whole must face.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 263-276